Building Epidemiological Capacity for Health Security in Liberia - Muhammad Shakir Balogun; Maame Amo Addae; Himiede Wede Wilson (Journal of Interventional Epidemiology and Public Health)
Liberia was the worst affected country in the 2014 Ebola Virus Disease (EVD) outbreak in West Africa. The outbreak exposed the systemic weaknesses in the healthcare system in the country.[1] One of the urgent gaps that needed to be quickly addressed was building a competent national epidemiologic workforce. The country needed a corps of well-trained healthcare workers who could promptly detect disease threats and respond in a timely manner. Therefore, in 2015, the US CDC in collaboration with Emory University and the African Field Epidemiology Network, established the Frontline Field Epidemiology Training Program (FETP) to build sub-national level capacity for surveillance and response by training healthcare workers in the counties and districts.[2] The graduates of the frontline FETP programme became the major targets of the intermediate programme when it was established in 2018. Liberia now has two of the three tiers of the FETP pyramid.